MRI Measurements of Left Ventricular Systolic Wall Thickening Compared to Regional Myocardial Perfusion as Determined by 201 Tl SPECT in Patients with Coronary Artery Disease - Kleinhans, E.; Altehoefer, C.; Arnold, C.; Buell, U.; Dahl, J. vom; Uebis, R. (Nuklearmedizin - NuclearMedicine, 1991)
Magnetic resonance imaging (MRI) of the left ventricle (LV) is an excellent method of measuring systolic wall thickening (SWT). The aim of the present study was (a) to describe a new approach for measurement of SWT and (b) to define the relationship between SWT and regional myocardial perfusion as determined by 201TI SPECT. 79 patients - 51 with and 28 without history of earlier myocardial infarction - underwent SPECT and, within the next two weeks, MRI. End-diastolic and end-systolic spin echo images were obtained by a reduced permutation technique. For MRI measurements, only long-axis sections through the LV in the equatorial plane were used. Slice orientation was selected according to the findings of SPECT, imaging the infarcted wall segment by single or double angulation. At 7 equidistant points around the LV wall SWT was measured and compared with the corresponding regional myocardial uptake values from SPECT in percent of maximal perfusion. Wall thickness of the anterior wall was normal. Because the majority of myocardial infarctions were posterior-inferior (55%), thickness of the posterior wall was markedly decreased. A close relationship of perfusion to SWT was found. Higher perfusion areas (>50% of maximal Tl uptake) corresponded with normal SWT (>3.0 mm), a marked decrease of SWT (<1 mm) was found in areas with perfusion deficits (<40%). Thus, a 201TI uptake value at rest of 41-50% of the respective myocardial maximum acts as a threshold by discriminating normal from severely reduced SWT.